2020
DOI: 10.3389/fpls.2020.605276
|View full text |Cite
|
Sign up to set email alerts
|

OsRRM, an RNA-Binding Protein, Modulates Sugar Transport in Rice (Oryza sativa L.)

Abstract: Sugar allocation between vegetative and reproductive tissues is vital to plant development, and sugar transporters play fundamental roles in this process. Although several transcription factors have been identified that control their transcription levels, the way in which the expression of sugar transporter genes is controlled at the posttranscriptional level is unknown. In this study, we showed that OsRRM, an RNA-binding protein, modulates sugar allocation in tissues on the source-to-sink route. The OsRRM exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Furthermore, expression in the nodes and stems has been thought to relate to cell proliferation/expansion and nutrient transport. For example, our previous study reported that a spin-like gene, OsRRM , which modulates sugar transport, had a similar expression profile to OsNAC129 in stems, and the osrrm mutant displayed reduced plant height and grain size, similar to the phenotypes observed in OsNAC129 -OE plants ( Liu et al, 2020 ). Very recently, another group reported that OsNAC129 and its interactor OsNAC127 do indeed participate in grain filling regulation by directly targeting sugar transporter genes including OsMST6 and OsSWEET4 ( Ren et al, 2021 ).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, expression in the nodes and stems has been thought to relate to cell proliferation/expansion and nutrient transport. For example, our previous study reported that a spin-like gene, OsRRM , which modulates sugar transport, had a similar expression profile to OsNAC129 in stems, and the osrrm mutant displayed reduced plant height and grain size, similar to the phenotypes observed in OsNAC129 -OE plants ( Liu et al, 2020 ). Very recently, another group reported that OsNAC129 and its interactor OsNAC127 do indeed participate in grain filling regulation by directly targeting sugar transporter genes including OsMST6 and OsSWEET4 ( Ren et al, 2021 ).…”
Section: Discussionmentioning
confidence: 77%
“…Southern blot analysis of the osnac129 mutant was performed as described previously ( Liu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several sugar transporters have been shown to be regulated posttranscriptionally by the RNA binding protein OsRRM. OsRRM is produced in anthers and has been shown to positively affect steady‐state transcript levels of a suite of transporter genes including MST6 and 8 , TMT1 and 2 , as well as four sucrose transporters SUT1 , 2 , 3 and 4 , probably by stabilising the respective mRNAs (Liu et al ., 2020). SWEET mRNA and protein levels have not been tested in these mutants, yet, based on the findings summarised above, it is tempting to speculate that SWEET11a and 11 b may be coregulated by the same mechanisms and may also be involved in temperature tolerance of male reproductive organs in rice.…”
Section: Discussionmentioning
confidence: 99%
“…3 and 4, probably by stabilising the respective mRNAs (Liu et al, 2020). SWEET mRNA and protein levels have not been tested in these mutants, yet, based on the findings summarised above, it is tempting to speculate that SWEET11a and 11b may be coregulated by the same mechanisms and may also be involved in temperature tolerance of male reproductive organs in rice.…”
Section: Interplay Of Sweet11a and 11b With Other Sugar Transporters ...mentioning
confidence: 99%
“…Several sugar transporters have been shown to be regulated posttranscriptionally by the RNA binding protein OsRRM. OsRRM is produced in anthers and has been shown to positively affect steady state transcript levels of a suite of transporter genes including MST6 and 8, TMT1 and 2, as well as four sucrose transporters SUT1,2, 3 and 4, likely by stabilizing the respective mRNAs (Liu et al, 2020).…”
Section: Interplay Of Sweet11a and B With Other Sugar Transporters And Cell Wall Invertasesmentioning
confidence: 99%